ANALISIS MANAJEMEN RISIKO PEMBIAYAAN KEPEMILIKAN RUMAH BERSUBSIDI SYARIAH PADA BANK ACEH SYARIAH CABANG JEURAM - Ridla Tarigan, Ismail Rasyid; Zahidi, Mohd; Ahmadsyah, Israk (Program Studi Perbankan Syariah FEBI UIN Ar-Raniry, 2024)
Risk in Subsidized Home Ownership Financing occurs when customers have difficulty paying financing due to irregular income. Therefore, the longer the financing period, the risk borne by the bank will increase. This study aims to analyze the application of risk management in preventing potential losses due to the large number of customers with irregular income. The method used is qualitative with a descriptive approach. Researchers used two data sources, namely primary data and secondary data. The results showed that the house could be built after going through the mechanism established by Bank Aceh Syariah Jeuram Branch. The application of risk management is carried out by analyzing 5C + 1S (Character, Capacity, Capital, Collateral, Condition of economy, and Sharia Compliance) due to differences in payment mechanisms and income receipts between customers with fixed and irregular income. Obstacles occur when Subsidized PKR customers want to apply for financing without meeting the requirements or do a murabaha contract before the house is ready to be occupied, so the bank needs to explain transparently so that risk management runs smoothly. Thus, overall risk management at Bank Aceh Syariah is in accordance with the DSN-MUI fatwa which is supervised by the Sharia Supervisory Board.